CXCL9:SPP1 macrophage polarity identifies a network of cellular programs that control human cancers - Bill, Ruben; Wirapati, Pratyaksha; Messemaker, Marius; Roh, Whijae; Zitti, Beatrice; Duval, Florent; Kiss, Máté; Park, Jong Chul; Saal, Talia M.; Hoelzl, Jan; Tarussio, David; Benedetti, Fabrizio; et al. (Science (American Association for the Advancement of Science), 2023)
Tumor microenvironments (TMEs) influence cancer progression but are complex and often differ between patients. Considering that microenvironment variations may reveal rules governing intratumoral cellular programs and disease outcome, we focused on tumor-to-tumor variation to examine 52 head and neck squamous cell carcinomas. We found that macrophage polarity—defined by CXCL9 and SPP1 (CS) expression but not by conventional M1 and M2 markers—had a noticeably strong prognostic association. CS macrophage polarity also identified a highly coordinated network of either pro- or antitumor variables, which involved each tumor-associated cell type and was spatially organized. We extended these findings to other cancer indications. Overall, these results suggest that, despite their complexity, TMEs coordinate coherent responses that control human cancers and for which CS macrophage polarity is a relevant yet simple variable. One of the challenges in studying human disease is that the same condition can manifest differently across patients. However, patient variation can also be a positive thing, revealing information about the composition of diseased tissues and the relationship to disease outcome. Bill et al . used patient-to-patient variations to study how tumor microenvironments influence the progression of head and neck squamous cell carcinoma. The authors found that variations in macrophage polarity, defined by the expression of two genes, CXCL9 and SPP1 , was a simple but critical feature of tumor microenvironments. The CXCL9:SPP1 ratio could characterize the abundance of antitumor immune cells in cancer, gene expression programs in each tumor-infiltrating cell type, the regulation of communication networks that dictate tumor control or progression, and the response to immunotherapy. —Priscilla N. Kelly A two-gene signature from the tumor microenvironment of head and neck squamous cell carcinoma can predict tumor response to immunotherapy.